1998
DOI: 10.1074/jbc.273.37.23740
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Human Hemoglobins with Increased Polarity in the α- or β-Heme Pocket

Abstract: The spectroscopic, conformational, and functional properties of mutant carbonmonoxy hemoglobins in which either the ␤-globin Val 67 (E11) or the ␣-globin Val 62 (E11) is replaced by threonine have been investigated. The thermal evolution of the Soret absorption band and the stretching frequency of the bound CO were used to probe the stereodynamic properties of the heme pocket. The functional properties were investigated by kinetic measurements. The spectroscopic and functional data were related to the conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Conformational changes in the protein, and planarization of the heme and iron are associated with the entry and binding of CO, for example. [9,35] In a carefully conducted study, Messori and co-workers found that artemisinin 1 induces a slow decay of the Soret band in Hb-Fe II (25 % in 24 h) heralded by an incipient slight blue shift. [36] Figure 3 a).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conformational changes in the protein, and planarization of the heme and iron are associated with the entry and binding of CO, for example. [9,35] In a carefully conducted study, Messori and co-workers found that artemisinin 1 induces a slow decay of the Soret band in Hb-Fe II (25 % in 24 h) heralded by an incipient slight blue shift. [36] Figure 3 a).…”
Section: Discussionmentioning
confidence: 98%
“…These data correspond to those previously recorded. [8,9] When a solution (0.1 mL) of artemisinin 1 in degassed dimethyl sulfoxide (DMSO, 10 mg mL À1 ) and diluted with degassed H 2 O (1:20, final concentration 0.5 mg mL À1 ) is added to the Hb-Fe II solution, the absorption at 406 nm becomes apparent within 10 min. The change is essentially complete within 60 min.…”
Section: Introductionmentioning
confidence: 99%
“…1). The importance of these residues on ligand binding has been studied by several groups (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Hemoglobin (Hb)mentioning
confidence: 99%
“…The first band is located at about 1950 cm À1 and is a fine probe of the distal heme pocket conformation; it has been used, e.g., to characterize the so-called taxonomic substates in MbCO [14] and to probe the orientation of the bound CO molecule [15][16][17] and/or the electrostatic environment of the heme [18]. For HbCO, the CO stretching band of the native protein and of several mutants has been studied [19,20]; for native human HbCO, the thermal behavior in the temperature interval of 300-10 K has also been investigated [21]. The effects of protein quaternary conformation on the peak position and shape of this band have been reported only for the mutant hemoglobin Kansas and for carp hemoglobin, with or without IHP [22], and for T-state human hemoglobin crystals at low CO saturation [23].…”
Section: Introductionmentioning
confidence: 99%